2005
DOI: 10.1002/ddr.10416
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of drug-loaded chitosan-tripolyphosphate microspheres by spray drying

Abstract: The present study reports on the preparation of chitosan-tripolyphosphate (TPP) microspheres by the spray-drying method using acetaminophen as a model drug substance. Chitosan-TPP microspheres were spherical and had a smooth surface. Perfectly spherical chitosan-TPP microparticles loaded with acetaminophen were obtained in the size range of 3.1-10.1 mm. Spray-dried chitosan-TPP microspheres were positively charged (zeta potential ranged from +18.4 to +31.8). The encapsulation efficiency of these microspheres w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
1
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 31 publications
9
81
1
8
Order By: Relevance
“…Further, it was observed that percentage of swelling decreased as the concentration of TPP was increased. The results were in agreement with previous studies (19,20). Table II shows the percentage entrapment efficiency of formulations.…”
Section: Swelling Studysupporting
confidence: 92%
“…Further, it was observed that percentage of swelling decreased as the concentration of TPP was increased. The results were in agreement with previous studies (19,20). Table II shows the percentage entrapment efficiency of formulations.…”
Section: Swelling Studysupporting
confidence: 92%
“…Some interesting drug delivery systems based on hydrogels have thus been proposed [5][6][7] . Among hydrogels, however, considerable research attention has been ORIENTAL JOURNAL OF CHEMISTRY www.orientjchem.org focused on so-called "smart" hydrogels which can transfer their volume in response to environmental stimuli, and these results in environmental stimuli modifying drug release.…”
Section: Introductionmentioning
confidence: 99%
“…It is biocompatible, biodegradable, easily formed into structures under mild processing conditions and can be chemically modified, so it is a natural choice as drugdelivery carrier [6,7], cartilage/skin tissue engineering Derm Matrix Composite Materials scaffolds [8][9][10], and regenerative membrane [11]. The physical properties of a polymer can be altered by introducing a second polymer that improves the properties of the original polymer in certain aspects, such as hydrophobility, cell compatibility.…”
Section: Introductionmentioning
confidence: 99%